Safety and Feasibility of Cephalic Venous Access for Cardiac Resynchronization Device Implantation. - Ussen, Bassey; Dhillon, Paramdeep S.; Anderson, Lisa; Beeton, Ian; Hickman, Mike; Gallagher, Mark M. (Pacing & Clinical Electrophysiology, 2011)
Cardiac resynchronization therapy (CRT) devices are usually implanted using subclavian vein access, which is associated with the risk of pneumothorax. We examined whether cephalic venous access is an effective alternative to subclavian access by the Seldinger technique for CRT delivery. We retrospectively analyzed all CRT procedures performed over a 1-year period at our center with respect to the access methods, primary success rate, safety, and efficiency. We retrospectively analyzed 103 consecutive primary implantation procedures. The procedure was accomplished using cephalic access alone for 54 of 61 (89%) CRT implants attempted by this route. The overall success rate was 100% (61/61) with additional use of subclavian access. CRT implantation via subclavian vein access was successful in 37 of 42 (88%) (P < 0.05 vs cephalic group). The procedure duration was shorter for the cephalic group (118 ± 39 vs 147 ± 36 minutes, P < 0.0005) as were the screening times and radiation exposure (15 ± 9 vs 27 ± 18 minutes and 4.7 ± 5.8 vs 9.3 ± 9.1 Gcm, both P < 0.01). In the cephalic group, procedure duration and radiation exposure diminished significantly with increasing experience of the technique. Complications occurred in two of 61 (3.3%) cases in the cephalic group and three of 42 (7.1%) in the subclavian group (P = NS). CRT devices can be implanted using cephalic access alone in a large majority of cases. This approach is safe and efficient. (PACE 2011; 34:365-369)